Protein tyrosine kinases in Schistosoma mansoni - Diana Bahia; Luiza Freire Andrade; Fernanda Ludolf; Renato Arruda Mortara; Guilherme Oliveira (Memorias do Instituto Oswaldo Cruz, 2006)
The identification and description of signal transduction molecules and mechanisms are essential to elucidate Schistosoma mansoni host-parasite interactions and parasite biology. This mini review focuses on recent advancements in the study of signalling molecules and transduction mechanisms in S. mansoni, drawing special attention to the recently identified and characterised protein tyrosine kinases of S. mansoni.